Malnutrition assessed by phase angle determines outcomes in low-risk cardiac surgery patients. Issue 6 (December 2016) - Ringaitiene, Donata; Gineityte, Dalia; Vicka, Vaidas; Zvirblis, Tadas; Norkiene, Ieva; Sipylaite, Jurate; Irnius, Algimantas; Ivaskevicius, Juozas
Summary: Background & aims: Phase angle (PA), which is obtained from bioelectrical impedance analysis (BIA), is a non-invasive method for measuring altered electrical properties of biological tissues. It has been recognised as an objective prognostic marker of disease severity and frailty. The aim of this study is to determine whether PA is a marker of malnutrition and postoperative morbidity in low operative risk patients undergoing cardiac surgery. Methods: A prospective study was conducted in a tertiary hospital. The nutritional state of the cardiac surgery patients was evaluated using BIA the day before the scheduled surgery. After applying selection criteria, 342 low operative risk patients were selected and classified into two groups in accordance with the PA value: a low PA group and a normal PA group. The correlation between low PA and low fat-free mass index (FFMI), a marker of malnutrition, was assessed. Associations between low PA and adverse postoperative outcomes, defined by the Society of Thoracic Surgeons postoperative risk evaluation model, were analysed. The impact of low PA on length of stay in an ICU and hospital was evaluated. Results: Low PA was detected in 61 (17.8%) patients in the selected group, which consisted of low operative risk patients with a median Euroscore II value of 1.46 (IQR: 0.97–2.03) and was associated with FFMI with Pearson's R of 0.515 (p < 0.001). Low PA was associated with higher rates (13 [21.3%] vs. 30 [10.7%] p = 0.023) and risk of postoperative morbidity in univariate regression analysis (OR = 2.27, Cl 95% = 1.10–4.66, p = 0.026). Furthermore, low PA persisted as an independent factor in multivariate regression analysis (OR = 2.50, CI 95% 1.18–5.29, p = 0.016) adjusted for preoperative risk factors of postoperative morbidity. Evaluation of hospitalisation length revealed a tendency of a prolonged hospitalisation (>14 days) rate (31 [50.8%] vs. 105 [37.8%], p = 0.063) in the group with low PA. Conclusion: A low preoperative PA is an indicator of malnutrition and determines adverse outcomes after cardiac surgery. Further research is needed to evaluate clinical applications of the PA, such as a more accurate identification of malnourished cardiac surgery patients.